2014
DOI: 10.1111/jbi.12302
|View full text |Cite
|
Sign up to set email alerts
|

Range‐wide ecological niche comparisons of parasite, hosts and dispersers in a vector‐borne plant parasite system

Abstract: Aim To test whether the distribution of the mistletoe Phoradendron californicum is mediated by host distributions (host niche hypothesis, HNH), or by factors such as the mistletoe's autecology (parasite niche hypothesis, PNH) or that of its vectors (vector niche hypothesis, VNH). Our null hypothesis is that the ecological niche of the mistletoe will not be distinct from that of its hosts or vectors; alternatively, mistletoe infections might appear in hosts only in regions where host distributions overlap suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
5
22
0
1
Order By: Relevance
“…The life cycle of parasitic angiosperms often involves interactions with multiple species. Therefore, these parasites represent ideal systems to test evolutionary hypotheses regarding host specificity, transmission and diversification (Kuijt, 1969(Kuijt, , 2009Esp ındola et al, 2014;Lira-Noriega & Peterson, 2014). Recent work, mainly in animals, has shown that parasitism is a major driver of species diversification (Wiens et al, 2015), and host switching has been considered to be the most common form of parasitic population divergence and speciation (de Vienne et al, 2013;Hoberg & Brooks, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of parasitic angiosperms often involves interactions with multiple species. Therefore, these parasites represent ideal systems to test evolutionary hypotheses regarding host specificity, transmission and diversification (Kuijt, 1969(Kuijt, , 2009Esp ındola et al, 2014;Lira-Noriega & Peterson, 2014). Recent work, mainly in animals, has shown that parasitism is a major driver of species diversification (Wiens et al, 2015), and host switching has been considered to be the most common form of parasitic population divergence and speciation (de Vienne et al, 2013;Hoberg & Brooks, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The works of Lira-Noriega et al (2015) and Lira-Noriega and Peterson (2014) on the mistletoe Phoradendron californicum have demonstrated that the distribution of this species is strongly affected by the evolutionary hot spots where the host, dispersal vectors and environmental condition of the mistletoes overlap. Their studies highlight the importance of the geological past interacting with the mistletoe–host associations in structuring phylogeography and initiating host races in mistletoes.…”
Section: Geographic Mosaic Approachmentioning
confidence: 99%
“…Their studies highlight the importance of the geological past interacting with the mistletoe–host associations in structuring phylogeography and initiating host races in mistletoes. Using herbarium voucher specimens, Lira-Noriega and Peterson (2014) tested three niche hypotheses (host, vector and parasite) that likely mediate mistletoe distribution and found that host availability alone does not determine mistletoe establishment. Instead, suitable environmental conditions for the mistletoe are a prerequisite.…”
Section: Geographic Mosaic Approachmentioning
confidence: 99%
See 2 more Smart Citations